Intradiscal treatment of the cartilage endplate for improving solute transport and disc nutrition - Habib, Mohamed; Hussien, Shayan; Jeon, Oju; Lotz, Jeffrey C.; Wu, Peter I-Kung; Alsberg, Eben; Fields, Aaron J. (Frontiers in Bioengineering and Biotechnology, 2023)
Poor nutrient transport through the cartilage endplate (CEP) is a key factor in the etiology of intervertebral disc degeneration and may hinder the efficacy of biologic strategies for disc regeneration. Yet, there are currently no treatments for improving nutrient transport through the CEP. In this study we tested whether intradiscal delivery of a matrix-modifying enzyme to the cartilage endplate (CEP) improves solute transport into whole human and bovine discs. Ten human lumbar motion segments harvested from five fresh cadaveric spines (38-66 years old) and nine bovine coccygeal motion segments harvested from three adult steers were treated intradiscally either with collagenase enzyme or control buffer that was loaded in alginate carrier. Motion segments were then incubated for 18 hr at 37C, the bony endplates removed, and the isolated discs were compressed under static (0.2 MPa) and cyclic (0.4-0.8 MPa, 0.2Hz) loads while submerged in fluorescein tracer solution (376 Da; 0.1 mg/mL). Fluorescein concentrations from site-matched nucleus pulposus (NP) samples were compared between discs. CEP samples from each disc were digested and assayed for sulfated glycosaminoglycan (sGAG) and collagen contents. Results showed that enzymatic treatment of the CEP dramatically enhanced small solute transport into the disc. Discs with enzyme-treated CEPs had up to 10.8-fold (human) and 14.0-fold (bovine) higher fluorescein concentration in the NP compared to site-matched locations in discs with buffer-treated CEPs (p < 0.0001). Increases in solute transport were consistent with the effects of enzymatic treatment on CEP composition, which included reductions in sGAG content of 33.5% (human) and 40% (bovine). Whole disc biomechanical behavior — namely, creep strain and disc modulus — was similar between discs with enzyme- and buffer-treated CEPs. Taken together, these findings demonstrate the potential for matrix modification of the CEP to improve the transport of small solutes into whole intact discs.